Wild rodents harbour high diversity of Arthroderma - Moulíková, Š; Kolařík, M; Lorch, J M; Kolarczyková, D; Hubka, V; Čmoková, A (Persoonia, 2023)
Arthroderma is the most diverse genus of dermatophytes, and its natural reservoir is considered to be soil enriched by keratin sources. During a study on the diversity of dermatophytes in wild small rodents in the Czech Republic, we isolated several strains of Arthroderma. To explore the diversity and ecological significance of these isolates from rodents (n = 29), we characterised the strains genetically (i.e., sequenced ITS, tubb and tef1α), morphologically, physiologically, and by conducting mating experiments. We then compared the rodent-derived strains to existing ITS sequence data from GenBank and the GlobalFungi Database to further investigate biogeography and the association of Arthroderma species with different types of environments. In total, eight Arthroderma species were isolated from rodents, including four previously described species (A. crocatum, A. cuniculi, A. curreyi, A. quadrifidum) and four new species proposed herein, i.e., A. rodenticum, A. simile, A. zoogenum and A. psychrophilum. The geographical distribution of these newly described species was not restricted to the Czech Republic nor rodents. Additional isolates were obtained from bats and other mammals, reptiles, and soil from Europe, North America, and Asia. Data mining showed that the genus has a diverse ecology, with some lineages occurring relatively frequently in soil, whereas others appeared to be more closely associated with live animals, as we observed in A. rodenticum. Low numbers of sequence reads ascribed to Arthroderma in soil show that the genus is rare in this environment, which supports the hypothesis that Arthroderma spp. are not soil generalists but rather strongly associated with animals and keratin debris. This is the first study to utilise existing metabarcoding data to assess biogeographical, ecological, and diversity patterns in dermatophytes. Citation: Moulíková Š, Kolařík M, Lorch JM, et al. 2022. Wild rodents harbour high diversity of Arthroderma. Persoonia 50: 27- 47. https://doi.org/10.3767/persoonia.2023.50.02.
Keywords: geophilic dermatophytes; GlobalFungi; wild rodents; new taxa; Arthroderma; polyphasic taxonomy; mating type genes